2020
DOI: 10.1021/jasms.0c00350
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Isomers by the 13C Shifts in Ion Mobility Spectra

Abstract: Mass spectrometry (MS) and isotopes were intertwined for a century, with stable isotopes central to many MS identification and quantification protocols. In contrast, the analytical separations including ion mobility spectrometry (IMS) largely ignored isotopes, partly because of insufficient resolution. We recently delineated various halogenated aniline isomers by structurally specific splitting in FAIMS spectra. While this capability hinges on the 13 C shifts, all preceding studies leveraged 37 Cl or 81 Br to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…While there have been fewer demonstrations of isotopologue and isotopomer separations with TWIMS, it is important to discuss contributions from groups utilizing other IMS-based techniques, such as field asymmetric ion mobility spectrometry. Additionally, it is necessary to mention that atmospheric pressure DTIMS has also been utilized to separate isotopologues of small molecules (e.g., acetone and benzene-like compounds). Notably, chloride isotopes, glycine isotopomers/isotopologues, and di-alanine isotopomers were resolved in early demonstrations of isotopic separations in FAIMS. ,, More recently, FAIMS-based studies of halogenated aniline rings (e.g., mono/di/tri-substituted aniline rings containing chlorine, bromine, and iodine atoms) have revealed that elemental and structurally specific isotopic shifts, as well as these isotopic shifts, are additive in nature. , While the physical nature of the FAIMS-based isotopic shifts remains unknown, the authors describe them as likely being a result of center of mass shifts (i.e., mass distribution-based shifts). , However, the unknown extent of ion heating at the high electric fields in FAIMS convolutes analysis, potentially contributing to the observed separation. Clearly, more future work is necessary to compare isotopic shifts in FAIMS with those in atmospheric DTIMS and TWIMS-based separations.…”
Section: Introductionmentioning
confidence: 99%
“…While there have been fewer demonstrations of isotopologue and isotopomer separations with TWIMS, it is important to discuss contributions from groups utilizing other IMS-based techniques, such as field asymmetric ion mobility spectrometry. Additionally, it is necessary to mention that atmospheric pressure DTIMS has also been utilized to separate isotopologues of small molecules (e.g., acetone and benzene-like compounds). Notably, chloride isotopes, glycine isotopomers/isotopologues, and di-alanine isotopomers were resolved in early demonstrations of isotopic separations in FAIMS. ,, More recently, FAIMS-based studies of halogenated aniline rings (e.g., mono/di/tri-substituted aniline rings containing chlorine, bromine, and iodine atoms) have revealed that elemental and structurally specific isotopic shifts, as well as these isotopic shifts, are additive in nature. , While the physical nature of the FAIMS-based isotopic shifts remains unknown, the authors describe them as likely being a result of center of mass shifts (i.e., mass distribution-based shifts). , However, the unknown extent of ion heating at the high electric fields in FAIMS convolutes analysis, potentially contributing to the observed separation. Clearly, more future work is necessary to compare isotopic shifts in FAIMS with those in atmospheric DTIMS and TWIMS-based separations.…”
Section: Introductionmentioning
confidence: 99%
“…This paradigm was initially developed utilizing the He/CO 2 buffers and protonated haloanilines with up to three Cl, Br, or I atoms at varied ring positions, producing three or six isomers ( m ∼ 130–330 Da). These species display MS features above the base peak by +1 Da (dominated by 13 C) and +2 Da (mostly due to 37 Cl, 81 Br, or 13 C 2 for the iodoanilines with monoisotopic halogen). Some isomers were distinguished by single E C shifts, and all were delineated by 2-D ( 13 C/ 37 Cl or 13 C/ 81 Br) shifts. , The shifts for all isotopic groups (save 13 C 2 in few cases) were additive as in normalΔ E normalC ( C 13 C 37 l ) = normalΔ E normalC ( C 13 ) + normalΔ E normalC ( C 37 l ) This permitted averaging several Δ E C values in same spectrum, up to n = 4 for 13 C in tribromoanilines (between m / z of 328 and 329 for sole 13 C, 330 and 331 for 13 C on top of 81 Br, 332 to 333 for 13 C on top of 81 Br 2 , and 334 to 335 for 13 C on top of 81 Br 3 ) . Such multiplexing reduces random Δ E C errors by ideally the factor of n 1/2 , enhancing the isomer demarcation. …”
Section: Introductionmentioning
confidence: 99%
“…Some isomers were distinguished by single E C shifts, and all were delineated by 2-D ( 13 C/ 37 Cl or 13 C/ 81 Br) shifts. , The shifts for all isotopic groups (save 13 C 2 in few cases) were additive as in normalΔ E normalC ( C 13 C 37 l ) = normalΔ E normalC ( C 13 ) + normalΔ E normalC ( C 37 l ) This permitted averaging several Δ E C values in same spectrum, up to n = 4 for 13 C in tribromoanilines (between m / z of 328 and 329 for sole 13 C, 330 and 331 for 13 C on top of 81 Br, 332 to 333 for 13 C on top of 81 Br 2 , and 334 to 335 for 13 C on top of 81 Br 3 ) . Such multiplexing reduces random Δ E C errors by ideally the factor of n 1/2 , enhancing the isomer demarcation. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations